Pollen morphology of the genus Impatiens L. (Balsaminaceae) and its systematic implications - Pechimuthu, Muthulakshmipechiammal; Arumugam, Rajendran; Ponnusamy, Samydurai (Acta Biologica Szegediensis, 2021)
Pollen morphology of 18 species from the genus Impatiens collected from diﬀerent localities in Nilgiris, Tamil Nadu was evaluated using scanning electron microscopy (SEM) during the period of February 2017 to November 2019. From the observation of pollen it was found to be structurally monad; prolate, sub-prolate and prolate-spheroidal in equatorial view; and circular, rectangular, triangular, quinquangular, elliptic and quadrangular in polar view. The apertures varied from dicolpate, tricolpate to tetracolpate. The main ornamentation type was reticulate in most of the species except Impatiens fruticosa which showed echinate ornamentation. The variations in pollen structure within the species were useful for the identiﬁcation and classiﬁcation of the genus Impatiens. The high structural diversity renders important taxonomic value for species diﬀerentiation.